Screening for Motor Dysgraphia in Public Schools - Marielza Regina Ismael Martins; José Alexandre Bastos; Angela Traldi Cecato; Maria de Lourdes Souza Araujo; Rafael Ribeiro Magro; Vinicios Alaminos (Jornal de Pediatria, 2013)
Objective: To screen for warning signs of dysgraphia in schoolchildren at the sixth grade of elementary school. Method: This was a descriptive, exploratory, cross-sectional cohort study performed with 630 schoolchildren assessed through the (adapted) Analytical Dysgraphia Inventory, which recognizes difficulties in writing through the tracing the graphics. Results: A total of 22% (n = 138) of the sample presented all indications of dysgraphia; the most prevalent indicator was ascending/descending/fluctuating lines (53.6%). When the indicators were correlated to gender, males showed a significant difference (p < 0.05) in most of them. Among the warning signs of co-occurrences, dyslexia was the most prevalent indicator (22%). Conclusion: Given the large number of warning signs of dysgraphia observed in schoolchildren, it is advisable to screen for these signs, in order to implement early interventions. Resumo: Objetivo: Rastrear sinais de alerta para a disgrafia em escolares do 6° ano do ensino fundamental. Método: Trata-se de um estudo descritivo, exploratório, de coorte transversal realizado com 630 escolares avaliados através do Inventário Disgráfico Analítico (adaptado), que reconhece as dificuldades da escrita através do traçado dos grafismos. Resultados: Em 22% (n = 138) da amostra apareceram todos os indicativos de disgrafia, sendo que o indicador mais prevalente foi o de linha ascendente/descendente/flutuante (53,6%). Se correlacionados os indicadores ao gênero,os meninos apresentaram diferença significativa (p < 0,05) na maioria deles. Dentre os sinais de alerta de co-ocorrências, a dislexia foi a que obteve maior indicador (22%). Conclusão: Considerando o grande número de sinais de alerta para disgrafia encontrados nos escolares, torna-se pertinente o rastreio para que uma intervenção precoce seja realizada. Keywords: Screening, Dysgraphia, Learning disorders, Palavras-chave: Rastreio, Disgrafia, Transtornos de aprendizagem